The Relationship Between Psychological Beliefs and Financial Well-being Among Working Adults in Malaysia - Hay, Jocelyn Hay Ying Xuan; Norasmiha Mohd Nor (Research in Management of Technology and Business, 2026)
Financial well-being is a growing field of research because working adults in Malaysia are experiencing growing living expenses and family financial pressures. The objective of the study is to investigate whether there is a relationship between psychological beliefs - subjective financial knowledge, financial attitudes and locus of control and financial well-being among Malaysian working adults. The study area is the ages of individuals between 18-60 years. The descriptive research design has been used; collection of data has been done using a survey questionnaire given to 150 working adults and a response rate of 69 percent. The data were analysed by the descriptive statistics and Spearman Rho correlation analysis. The results indicate that subjective financial knowledge and locus of control are significantly positively related to financial well being and financial attitudes do not have any significant relationships. In general, participants are moderately financially well-being. Finally, the research indicates the significance between financial confidence and perceived control that enhance the financial well-being of employed Malaysians.